(3GdeTQhY GdeTJQc hSjdI dfbd GdJcfhdhLjG ai GdGQOf (B: s (3OQGSI ebGQfI (B/ s - (3YeQ adGM HNjJ GdYWjfs; (3SejMI GdbdjhHjs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2006)
(3jYJHQ GdeTQhY GdeTJQc GMO YbhO GdJLGQI GdOhdjI MjK Gfg jgOa Gdi GfTGA efTGI OGFeI Hjf GWQGa efJejf Gdi Ohd eNJdaI dJMbjb eUGdMgejeJGR HGfg YbO edRe GdLGfHjf (B: (3heMOO GdeOI (B: (3hYbO JYGhf (B: (3heSJbdjYJHQ GMO QcGFR fbd GdJcfhdhLjG GdJi JeJGR HGfgG edReI ddLGfHjf (B: (3hPGJ WHjYI NGUI (B: (3hYbO Tcdj (B: (3hef YbhO GdeYGhVI gh ef GdGdjGJ GdbGfhfjI GdeSJNOeI dfbd GdJcfhdhLjG ef NdGd GdGSJKeGQ GdOhdi GdeHGTQ (B: (3hGdYbhO cGOGI dfbd GdJcfhdhLjG hjbY Ydi YGJb ehQO GdJcfhdhLjG GdJRGe Hfbd JcfhdhLjG (B: (3hJbOje GdeSGYOI GdafjI (B: (3hVeGf GdJcfhdhLjG (B: (3hGdJHUjQ (B: (3hGdeMGaXI Ydi GdSQjI ceG jbY Ydi eSJhQO GdJcfhdhLjG GdGdJRGe HGOGA GdebGHd (B: (3hGSJNOGe GdYGedjf Ydi bOQI ef GdOQGjI jfbVi GdeTQhY GdeTJQc HGfbVGA GdeOI (B: (3hgdGc GdeTQhY (B: (3hGJaGb GdTQcGA (B: (3hGdJGejejYJHQ GdJMcje GdJLGQi GdOhdi GMO WQb aV GdefGRYGJ ai GdeTQhY GdeTJQc (B: (3Gdi LGfH GdbVGA GdhWfi ai MGdI YOe GdGJaGb Ydi GdJMcjes
(3jTJed Ydi edGMb(B: (3UaMI (B316-330s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQi, (B2006s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B341-360s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdJLGQjs; (3GdGQOfs; (3GdJcfhdhLjGs; (3GdeTQhY GdeTJQcs; (3TQcI GdeMGUIs; (3GdTQcI PGJ GdeSFhdjI GdeMOhOIs; (3GdGSJKeGQ GdOhdi GdeHGTQs; (3GdeTGQjY GdeTJQcI GdYQHjIs; (3GdJMcjes; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs